00 upvotes00 downvotes

49 views5 pagesTest on simultaneous equations and the quadratic formula (answers provided).

Feb 05, 2015

© © All Rights Reserved

DOCX, PDF, TXT or read online from Scribd

Test on simultaneous equations and the quadratic formula (answers provided).

© All Rights Reserved

49 views

00 upvotes00 downvotes

Test on simultaneous equations and the quadratic formula (answers provided).

© All Rights Reserved

You are on page 1of 5

Time: 30 minutes

Marks: 29

Name:

Question 1

Solve the simultaneous equations by using the elimination method.

1. 3x + 4y = 17

6x + y = 20

[3]

2. 2x + 3y = 14

3x + 2y = 11

[3]

3. 4x + 3y = 26

3x - 5y = -24

[3]

4. 4x - 3y = 2

5x + 7y = -19

[3]

Question 2

Solve the following quadratic equations using the quadratic formula.

1. x2 + 9x + 4=0

2. 2x2 + 3x - 7 = 0

3. 9x2 + 5x - 2 = 0

[4]

[4]

[4]

How do you feel you did in the test? Tick the box which best represents you.

Test was easy

Test was fine. I know I passed

I did not pass

If you think you did not pass, what do you think you can do next time to be more prepared?

________________________________________________________

________________________________________________________

________________________________________________________

________________________________________________________

Answers

Question 1

1. 3x + 4y = 17

6x + y = 20

We need to make the coefficients of one of the variables (either x or y) the same in both equations. We can

make the coefficients of x the same by multiplying the first equation by 2.Doing this we get:

6x + 8y = 34

6x + y = 20

Now that the coefficients of x are the same, we can now subtract these two equations. Doing this we get:

7y = 14

Solving for y (by diving both sides by 7) we get:

y = 2

Now we take this value of y and substitute it into either one of our original equations and then solve for x.

Subbing this value into our first equation we get:

3x + 4y = 17

3x + 4(2) = 17

3x = 9

x = 3

(divided by 3)

2. 2x + 3y = 14

3x + 2y = 11

We need to make the coefficients of one of the variables (either x or y) the same in both equations. We can

make the coefficients of x the same by multiplying the first equation by 3 and the second one by 2.Doing

this we get:

6x + 9y = 42

6x + 4y = 22

Now that the coefficients of x are the same, we can now subtract these two equations. Doing this we get:

5y = 20

Solving for y (by diving both sides by 5) we get:

y = 4

Now we take this value of y and substitute it into either one of our original equations and then solve for x.

Subbing this value into our first equation we get:

2x + 3y = 14

2x + 3(4) = 14

2x = 2

x = 1

(divided by 2)

3. 4x + 3y = 26

3x - 5y = -24

We need to make the coefficients of one of the variables (either x or y) the same in both equations. We can

make the coefficients of x the same by multiplying the first equation by 3 and the second one by 4.Doing

this we get:

12x + 9y = 78

12x - 20y = -96

Now that the coefficients of x are the same, we can now subtract these two equations. Doing this we get:

29y = 174

Solving for y (by diving both sides by 29) we get:

y = 6

Now we take this value of y and substitute it into either one of our original equations and then solve for x.

Subbing this value into our first equation we get:

4x + 3y = 26

4x + 3(6) = 26

4x = 8

x = 2

(divided by 2)

4. 4x - 3y = 2

5x + 7y = -19

We need to make the coefficients of one of the variables (either x or y) the same in both equations. We can

make the coefficients of x the same by multiplying the first equation by 3 and the second one by 4.Doing

this we get:

20x - 15y = 10

20x + 28y = -76

Now that the coefficients of x are the same, we can now subtract these two equations. Doing this we get:

-43y = 86

Solving for y (by diving both sides by 13) we get:

y = -2

Now we take this value of y and substitute it into either one of our original equations and then solve for x.

Subbing this value into our first equation we get:

4x - 3y = 2

4x - 3(-2) = 2

4x =-4

x = -1

(divided by 2)

Question 2

2

1. x + 9x + 4=0

In this case we have a=1, b=9 and c=4.

So using our formula:

x=

b b24 ac

2a

( 9 ) ( 9 ) 4 ( 1 )( 4 )

x=

2( 1)

2

x=

( 9 ) 65

2(1)

x=

( 9 )+ 65

2 (1)

= -0.47

Or

x=

( 9 ) 65

2(1)

= -8.53

2

2. 2x + 3x - 7 = 0

In this case we have a=2, b =3 and c = -7.

So using our formula:

x=

b b24 ac

2a

( 3 ) ( 3 ) 4 ( 2 ) (7 )

x=

2 (2)

2

x=

( 3 ) 65

2(2)

x=

( 3 ) + 65

2 (2)

Or

= 1.27

x=

( 3 ) 65

2(2)

= -2.77

2

3. 9x + 5x - 2 = 0

In this case we have a=9, b =5 and c = -2.

So using our formula:

x=

b b24 ac

2a

( 5 ) ( 5 ) 4 ( 9 )(2 )

x=

2( 9)

2

x=

( 5 ) 97

2(9)

x=

( 5 ) + 97

2 (9)

= 0.27

Or

x=

( 5 ) 97

2(9)

= -0.82

## Much more than documents.

Discover everything Scribd has to offer, including books and audiobooks from major publishers.

Cancel anytime.